Imaginaries of connectivity the creation of novel spaces of governance - Lobo-Guerrero, Luis; Alt, Suvi; Meijer, Maarten, 1993- (Global Epistemics series, 2020)
"This edited collection addresses the problem of how the creation of novel spaces of governance relates to imaginaries of connectivity in time. While connectivity seems almost ubiquitous today, it has been imagined and practiced in various ways and to varying political effects in different historical and geographical contexts"--